2021
DOI: 10.3390/audiolres11010011
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of Adults with Hearing Loss in the United States

Abstract: Purpose: The purpose of this study was to identify the current health status of adults in the United States with self-reported hearing loss and compare it with US adults with a self-reported excellent or good hearing in three areas: (1) chronic disease states and general health status, (2) medical screening behaviors, and (3) lifestyle behaviors. Methods: A secondary data analysis was conducted using the 2014 data set from the National Health Interview Survey (NHIS), specifically the Sample Adult Public Use Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…90,91 In addition to social isolation, hearing loss' impact on physical activity may be due to increased cognitive load (the amount of information one can process at any given time), walking limitations, reduced gait speed, fear of losing or breaking hearing devices, inability to hear surroundings/individuals, safety concerns, and the social stigma of hearing loss. 87,88,[92][93][94] This lack of physical activity may also contribute to frailty among older individuals. In crosssectional studies, hearing loss is associated with an 87% increase in the risk of frailty (risk ratio [RR]: 1.87; 95% confidence interval: 1.63-2.13) and 56% among longitudinal studies (RR: 1.56; 95% confidence interval: 1.29-1.88).…”
Section: Impairmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…90,91 In addition to social isolation, hearing loss' impact on physical activity may be due to increased cognitive load (the amount of information one can process at any given time), walking limitations, reduced gait speed, fear of losing or breaking hearing devices, inability to hear surroundings/individuals, safety concerns, and the social stigma of hearing loss. 87,88,[92][93][94] This lack of physical activity may also contribute to frailty among older individuals. In crosssectional studies, hearing loss is associated with an 87% increase in the risk of frailty (risk ratio [RR]: 1.87; 95% confidence interval: 1.63-2.13) and 56% among longitudinal studies (RR: 1.56; 95% confidence interval: 1.29-1.88).…”
Section: Impairmentsmentioning
confidence: 99%
“…Social isolation and hearing loss have also been linked with decreased physical activity. Adults with hearing loss are less likely to participate in physical activity 87‐89 and tend to be more sedentary 90,91 . In addition to social isolation, hearing loss’ impact on physical activity may be due to increased cognitive load (the amount of information one can process at any given time), walking limitations, reduced gait speed, fear of losing or breaking hearing devices, inability to hear surroundings/individuals, safety concerns, and the social stigma of hearing loss 87,88,92‐94 .…”
Section: Health Care Burdenmentioning
confidence: 99%
“…Despite the vast plethora of research on alcohol use in the general college population, research on alcohol use with deaf and hard of hearing individuals and college students is limited. In the existing studies, researchers found that alcohol use for deaf and hard of hearing individuals ranged from 33-75% (e.g., Anderson et al, 2018;Glassman et al, 2021;Hackett et al, 2016;Kushalnagar et al, 2019;Pinquart & Pfeiffer, 2015) compared to 56% of hearing people (Pinquart & Pfeiffer, 2015). Several studies identified that alcohol use is generally the same, except deaf and hard of hearing individuals are more likely to drink higher amounts when they do use (Anderson et al, 2018;Kushalnagar et al, 2019;Pinquart & Pfeiffer, 2015) and possibly may have more substance disorders as a result (McKee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%